Implementing a non-steroidal anti-inflammatory drugs communication bundle in remote and rural pharmacies and dispensing practices. Issue 3 (21st July 2018) - Morrison, Clare; Beauchamp, Tracy; MacDonald, Helen; Beattie, Michelle
Abstract : Non-steroidal anti-inflammatory drugs (NSAIDs) are associated with more emergency hospital admissions due to adverse drug reactions than any other class of medicine. One way to tackle this is to ensure that patients understand how to take their NSAIDs in the safest way possible. The aim of this project was to ensure that key safety information is given to every patient, every time an NSAID is sold or dispensed. The project started as part of the Scottish Patient Safety Programme's Pharmacy in Primary Care Collaborative. An NSAIDs bundle was developed, tested and implemented using the Model for Improvement as a framework, including multiple Plan, Do, Study, Act cycles. The bundle, and associated improvement package, was developed during phase I of the project and tested by seven teams (five pharmacies and two dispensing practices). Phase II tested the spread of the defined improvement package across an additional five community pharmacies and eight dispensing general practitioner practices. The project has resulted in the development of a simple package to improve communication with patients about NSAIDs, which should enable patients to take NSAIDs safely. Three key safety messages were developed, typical for a care bundle approach, and simple tools were employed to ensure every patient received these three key messages every time. The project aim of 95% compliance with the NSAIDs bundle within the seven initial sites by December 2015 was achieved (when an exclusion was applied). The spread of the defined improvement package to a further 13 sites was achieved by December 2016. By December 2017, all 81 community pharmacies in National Health Service (NHS) Highland had agreed to implement the NSAIDs bundle. In June 2018, a national NSAIDs bundle, based on the NHS Highland work, was introduced in community pharmacies across Scotland. We also believe that the approach could be replicated for other high-risk medicines.